Pengaruh Perbandingan Jumlah Starter dan Konsentrasi Agar pada Pembuatan Yogurt dari Sari Biji Nangka - Joko Purnomo; Syakir Naim Siregar (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2018)
The aim of this study to determine the effect of adding the amount of Starter and Agar concentration to yogurt of jackfruit seed juice. Total of Starters (S) consisting of 4 levels, namely: S1 = 2%, S2 = 4%, S3 = 6% and S4 = 8%. The second factor is Concentration of Agar (A) which consists of 4 levels, namely: A0 = 0%, A1 = 0.3%, A2 = 0.6% and A3 = 0.9%. Parameters observed included: yield, TSS, pH, organoleptics (color, taste, and texture). The results of statistical analysis showed that the number of static concentrations had a very significant effect (P <0.01) on yield, TSS, pH and taste, but did not differ significantly (P <0.05) on color and texture. The amount of agar concentration had a very significant effect (P <0.01) on yield, TSS and texture, but it was not significantly different (P <0.05) on pH, color and taste.